2013
DOI: 10.1002/asi.22816
|View full text |Cite
|
Sign up to set email alerts
|

Young people, child pornography, and subcultural norms on the Internet

Abstract: Literature to date has treated as distinct two issues (a) the influence of pornography on young people and (b) the growth of Internet child pornography, also called child exploitation material (CEM). This article discusses how young people might interact with, and be affected by, CEM. The article first considers the effect of CEM on young victims abused to generate the material. It then explains the paucity of data regarding the prevalence with which young people view CEM online, inadvertently or deliberately.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 39 publications
(65 reference statements)
0
17
0
Order By: Relevance
“…These experiences are significant contributing factors in developing sexual maladaptive behaviors (Creeden, 2013;Hunter, Figueredo, & Malamuth, 2010;Netland & Miner, 2012;Prichard, Spiranovic, Watters, & Lueg, 2013;Worling, 2005). Schwartz, Cavanaugh, Prentky, and Pimental (2006) confirmed that a high number of adolescents with sexual behavior problems and aggression have experienced similar life situations.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These experiences are significant contributing factors in developing sexual maladaptive behaviors (Creeden, 2013;Hunter, Figueredo, & Malamuth, 2010;Netland & Miner, 2012;Prichard, Spiranovic, Watters, & Lueg, 2013;Worling, 2005). Schwartz, Cavanaugh, Prentky, and Pimental (2006) confirmed that a high number of adolescents with sexual behavior problems and aggression have experienced similar life situations.…”
Section: Discussionmentioning
confidence: 98%
“…He readily admitted that pornography caused him a great deal of trouble and influenced him to seek sexual activity. Exposure to pornography, neglect, and abuse has been found to contribute to development of maladaptive sexual behaviors in adolescents (Hunter et al, 2010;Prichard et al, 2013;Schwartz et al, 2006). While many individuals who endure sexual abuse or view pornography do not necessarily go on to sexually offend, the prevalence of these conditions does speak to the importance of considering sexual addictions as well as trauma focused intervention.…”
Section: Early Exposure To Pornography and Sexualitymentioning
confidence: 99%
“…Advertising does not need to be limited to commercial, for-profit sites: much CEM is traded and "advertised" on P2P search sites, where it can be downloaded for free, facilitated by the appropriate choice of keywords [22]. Indeed, as shown by [8], searches for CEM on one of the most popular P2P search engines were more popular than Harry Potter movies during the time of their initial release.…”
Section: Advertising and Child Exploitation Materialsmentioning
confidence: 99%
“…This report, among others, lists all of the URLs removed from the Google Index, whenever a complaint from a rightsholder is upheld, i.e., when Google determines that the URL does contain or links to allegedly pirated material. 8 In the United States, this process is governed by the Digital Millennium Copyright Act (DMCA). It is interesting to note that the number of complaints upheld by Google almost doubles every year.…”
Section: Most Complained About Sitesmentioning
confidence: 99%
“…Parents need to be aware that this is the type of content that will be served up to their children, even if they are only intending to download torrent for music or less offensive content. The absence of traditional regulatory mechanisms for effectively controlling online content -including the Classification Board and Advertising Standards Bureau -mean that new subcultural norms are rapidly being established online, and these can have profoundly negative consequences; for example, a progression model of rising interest in child exploitation material has been linked to the rise of the online porn culture, particularly where young users are inadvertently exposed to pornography through advertising (Prichard et al, 2013).…”
mentioning
confidence: 99%